PENGARUH KEPEMIMPINAN DAN REWARD KERJA TERHADAP KINERJA KARYAWAN PADA PT ISS INDONESIA DIVISI CLEANING SERVICE PERMATA BANK BINTARO TANGERANG SELATAN - Saprudin, Udin; Irawati, Laila; Sutarto, Bambang (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2025)
This study aims to determine the effect of leadership and work motivation on employee performance at PT. ISS Indonesia Cleaning Service Division at Permata Bank Bintaro, South Tangerang. The method used is associative quantitative. The sampling technique used was saturated sampling and the sample in this study was 61 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing using SPSS software version 26. Hypothesis test obtained t count > t table or (3,697 > 2,001). The hypothesis test obtained by the value of t count > t table or (4,872 > 2,001). leadership and work motivation simultaneously have a positive and significant effect on employee performance with the regression equation Y = 15.666 + 0.191X1 + 0.386X2, the correlation value or the level of relationship between the independent variable and the dependent variable is obtained at 0.598, meaning it has a moderate relationship. The value of the coefficient of determination or contribution to its influence simultaneously is 35.7% while the remaining 64.3% is influenced by other factors. Hypothesis testing obtained F count > F table or (16.106 > 3.160). Thus H0 is rejected and H3 is accepted. This means that there is a significant influence simultaneously leadership and work motivation on employee performance.